Pengaruh Model Pembelajaran Kooperatif Tipe Group Investigation (GI) terhadap Kemampuan Pemahaman Konsep Matematika Siswa - Serli, Serli; Rahmat, Tasnim; Risnawita, Risnawita; Fitri, Haida (Lembaga Yasin AlSys, 2025)
This research was motivated by the problem of students' low ability to understand mathematical concepts, this can be seen from students' difficulties in solving problems that are different from the examples presented by the teacher. One effort to overcome this, researchers tried to apply a group investigation type cooperative learning model. This research aims to determine the significant influence of the group investigation type cooperative learning model on students' understanding of mathematical concepts. This type of research is pre-experimental with a research design, namely the static group comparison design. The population in this study was all class VIII MTs S Muhammadiyah Lawang Tigo Balai. The sample in this study was class VIII2 as the experimental class and class VIII3 as the control class. The instrument used in the research was a test of the ability to understand mathematical concepts in the form of a description test. Data obtained from research results based on data analysis using the t-test can be concluded that